Down Streaming & Industrial Revolution 4.0 In Sabah: An Overview - Rafiq Idris (Universiti Kebangsaan Malaysia, 2021)
Since gaining independence in 1963, Sabah economy has expanded gradually and become more diversified. From an economy that is heavily dependent on agriculture, fishery and forestry sector, the economy's GDP is currently also contributed by other important sectors like services, mining, and quarrying, manufacturing, and construction. Despite the expansion, the state is still far away from reaching high-income status. In this regard, this paper argues, to reach high-income status faster, the economy must increase down streaming activities, support and facilitate the adoption of IR4.0 and give attention to creative economic activities. All these, together with other contributing factors such as huge investment inflow, bigger annual federal allocation, conducive policy for business, and investment among others will help in expanding Sabah's economy faster.